2015
DOI: 10.1245/s10434-015-4629-6
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Mastectomy: Doubling Down on Complications?

Abstract: Complications after breast cancer surgery can result in increased hospitalization, additional surgical and medical interventions, increased costs, and delays in initiating recommended adjuvant treatment. Moreover, complications may lead to long-term emotional distress and patient dissatisfaction. Thus, accurate information regarding the risk, severity, and timing of postoperative complications must be clearly presented to breast cancer patients. In the accompanying study by Silva and colleagues, the authors us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Regarding patients with contralateral prophylactic mastectomy in unilateral BC indication, although there are still limited data on this subject, historically, these cases have a more extended hospital stay than to breast-conserving surgery or unilateral mastectomy and have more postsurgery visits and higher rates of hospitalization. 77 This potential increase in patient exposure could lead to a greater risk of infection by COVID-19 disease. 25 The expert panel suggested that a contralateral prophylactic mastectomy is not recommended during this period, and conservative breast surgery or even unilateral mastectomy should be carried out instead.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding patients with contralateral prophylactic mastectomy in unilateral BC indication, although there are still limited data on this subject, historically, these cases have a more extended hospital stay than to breast-conserving surgery or unilateral mastectomy and have more postsurgery visits and higher rates of hospitalization. 77 This potential increase in patient exposure could lead to a greater risk of infection by COVID-19 disease. 25 The expert panel suggested that a contralateral prophylactic mastectomy is not recommended during this period, and conservative breast surgery or even unilateral mastectomy should be carried out instead.…”
Section: Resultsmentioning
confidence: 99%
“…BCS is associated with lower rates of hospital stay and visits after surgery and hospitalization than mastectomy 77 : a study with patients undergoing nipple-sparing mastectomy had total complication rates of 47% and reoperations around 9%. 78 Regarding the use of oncoplastic surgery, complication rates also tend to be higher than in BCS.…”
Section: Resultsmentioning
confidence: 99%
“…Complication rates for skin-sparing mastectomy range from 6% to 42%, and have been found to be as high as 69.1% if including patients undergoing bilateral mastectomy with immediate reconstruction. 10,11 Differences in complication rates also vary by the data source used, with the National Surgical Quality Improvement Program often reporting complication rates for breast surgery that are lower than those reported in retrospective institutional reviews or claims-based data. [11][12][13][14][15] We report an overall complication rate of 15.7% per ISM, generally in line with the accepted ranges in the literature and also in line with a contemporary institutional cohort complication rate of 20.7%.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Differences in complication rates also vary by the data source used, with the National Surgical Quality Improvement Program often reporting complication rates for breast surgery that are lower than those reported in retrospective institutional reviews or claims-based data. [11][12][13][14][15] We report an overall complication rate of 15.7% per ISM, generally in line with the accepted ranges in the literature and also in line with a contemporary institutional cohort complication rate of 20.7%. The skin necrosis rate of 8.2% in the ISM cohort was also similar to that of the mastectomy with reconstruction cohort of 7.4% and is consistent with a reported rate of 13% for patients undergoing mastectomy with immediate reconstruction by Petersen et al 10 The infection rate of 0.8% in the ISM cohort was lower than the 5.9% in the mastectomy with reconstruction cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding patients with contralateral prophylactic mastectomy in unilateral breast cancer indication, although there is still limited data on this subject, historically these cases have a longer hospital stay compared to breast-conserving surgery or unilateral mastectomy, and also have more post-surgery visits and higher rates of hospitalization 57 . This potential increase in patient exposure could lead to a greater risk of infection by COVID-19 25 .…”
Section: Bilateral Mastectomymentioning
confidence: 99%